Pengembangan Sistem Informasi Manajemen Dinda Salon Di Kota Malang Berbasis Website - Riska Octaviani; Faizatul Amalia; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Dinda salon is a business form engaged in the beauty sector, which deals with special care services for women in Malang. The salon owner explained that the management of customer care data, which is still done manually, is recorded in books, making it difficult for employees to manage customer data and produce salon reports. Especially for treatment orders via reservation, customers have to come to the salon first, which certainly makes it difficult for customers. This research will discuss about how data is carried out optimally, being able to process customer data, maintenance data, promo data and reservation data by creating a website-based application. The customer makes a reservation to fill in customer data and it will automatically be stored in the database. Admin can also share promo info via SMS Gateway. This research uses the prototyping method. In the process of collecting data using interviews with the salon owner. Then the design stage is carried out on a system based on object oriented design and UML (Unified Modeling Language) modeling for the process of implementing a system using PHP as a programming language and the CodeIgniter Framework. The test used is the white-box testing method using pathway testing as a unit test. The black-box testing method is used as a validation test, with valid results obtained, for user acceptance testing, valid results are obtained from 43 test cases. Non-functionality testing, namely compatibility, the system can run properly through different browsers on Goegle and Mozilla Firefox.